2017
DOI: 10.1111/dom.12945
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of postprandial glucose by lixisenatide vs sitagliptin treatment in Japanese patients with type 2 diabetes on background insulin glargine: A randomized phase IV study (NEXTAGE Study)

Abstract: AimTo evaluate the pharmacodynamics of lixisenatide once daily vs sitagliptin once daily in Japanese patients with type 2 diabetes receiving insulin glargine U100.Materials and methodsThis multicentre, open‐label, phase IV study (NEXTAGE Study; ClinicalTrials.gov number, NCT02200991) randomly assigned 136 patients to either lixisenatide once daily via subcutaneous injection (10 µg initially increased weekly by 5 up to 20 µg) or once‐daily oral sitagliptin 50 mg. The primary endpoint was the change in postprand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Those responders have achieved the targeted HbA1c <7% with no symptomatic hypoglycemic episode after three months of intensification therapy and no weight gain. On the other hand,the numbers of hypoglycemic events reported with Lixisenatide were less than with the other intensification therapies in line with other clinical studies [25]. In addition, patients' body weight has significantly decreased after three months of Lixisenatide intensification therapy.…”
Section: Discussion:-supporting
confidence: 81%
“…Those responders have achieved the targeted HbA1c <7% with no symptomatic hypoglycemic episode after three months of intensification therapy and no weight gain. On the other hand,the numbers of hypoglycemic events reported with Lixisenatide were less than with the other intensification therapies in line with other clinical studies [25]. In addition, patients' body weight has significantly decreased after three months of Lixisenatide intensification therapy.…”
Section: Discussion:-supporting
confidence: 81%
“…Incretin-based drugs have been found to differ in efficacy with regard to limiting the postprandial increase in glucose concentration. Lixisenatide was thus shown to reduce postprandial glucose to a significantly greater extent compared with sitagliptin [ 18 , 19 ]. Vildagliptin also reduced both the mean amplitude of glycemic excursions and postprandial glucose to a significantly greater extent than sitagliptin [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 Delayed gastric emptying is not seen in the dipeptidyl peptidase IV inhibitors, which would suggest less appetite suppression compared with GLP-1 agents. 49,50 Adult studies of sitagliptin in T1DM have shown some promise in reducing total daily insulin dose. 51,52 Both studies were limited in sample size and duration.…”
Section: Non-insulinsmentioning
confidence: 99%